2020
DOI: 10.5713/ajas.19.0798
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk yield in imported Jersey and Jersey-Friesian cows using daily milk records in Sri Lanka

Abstract: Objective: Estimate genetic parameters for milk yield traits using daily milk yield records from parlour data generated in an intensively managed commercial dairy farm with Jersey and Jersey-Friesian cows in Sri Lanka. Methods: Genetic parameters were estimated for first and second lactation predicted and realized 305-day milk yield using univariate animal models. Genetic parameters were also estimated for total milk yield for each 30day intervals of the first lactation using univariate animal models and for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In support, Sarkar et al [ 2 ] demonstrated that cows fed TMR briquettes produced more milk than cows fed fresh forages supplemented with concentrates. The average milk production of our cows falls within the range (6 to 10 kg/d) of Sahiwal × Jersey cows [ 33 ], but is lower than purebred Jersey cows in Sri Lanka [ 34 ]. Milk protein yield tended to increase by 15% ( p = 0.091) for TMR briquettes vs. CTL, possibly because of the increased milk yield, as milk protein concentrations were similar among treatments ( p = 0.244).…”
Section: Resultsmentioning
confidence: 99%
“…In support, Sarkar et al [ 2 ] demonstrated that cows fed TMR briquettes produced more milk than cows fed fresh forages supplemented with concentrates. The average milk production of our cows falls within the range (6 to 10 kg/d) of Sahiwal × Jersey cows [ 33 ], but is lower than purebred Jersey cows in Sri Lanka [ 34 ]. Milk protein yield tended to increase by 15% ( p = 0.091) for TMR briquettes vs. CTL, possibly because of the increased milk yield, as milk protein concentrations were similar among treatments ( p = 0.244).…”
Section: Resultsmentioning
confidence: 99%
“…The values for lactation curve parameters were derived from the curve parameters of 305‐day milk yield described in the study by Samaraweera et al. (2020). For a given calving interval (CI, days), a lactation length (LL, days) of CI60 was assumed, with 60 days being the dry period.…”
Section: Methodsmentioning
confidence: 99%
“…where values for initial milk yield (a), increasing slope (b) and decreasing slope (c) were assumed to be as 12.5 kg, 0.1465 and 0.003 respectively. The values for lactation curve parameters were derived from the curve parameters of 305-day milk yield described in the study by Samaraweera et al (2020). For a given calving interval (CI, days), a lactation length (LL, days) of CI − 60 was assumed, with 60 days being the dry period.…”
Section: Derivation Of Economic Valuesmentioning
confidence: 99%
See 2 more Smart Citations